Caregiver-Reported ADHD in Shanghai, China: Prevalence, Associated Factors, and Implications for Diagnosis - Wang S; Zhang M; Huang L; Zhang X; Xue Z (Neuropsychiatric Disease and Treatment)
Shuxia Wang,1,* Mengxi Zhang,2,* Lirong Huang,1,* Xinguang Zhang,1 Zheng Xue1 1Department of Pediatrics, Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Health Systems and Implementation Science, Virginia Tech Carilion School of Medicine, Blacksburg, VA, USA*These authors contributed equally to this workCorrespondence: Zheng Xue; Shuxia Wang, Department of Pediatrics, Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, No. 68 Ronglian Road, Jiading District, Shanghai, 201800, People’s Republic of China, Tel +86 21 56639828, Email xuezheng@shutcm.edu.cn; grace_wang1983@126.comPurpose: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders among children and adolescents, while recent distribution of the disease has not been widely studied in China. This study aimed to examine the prevalence of caregiver-reported ADHD in Shanghai, China, and identify associated factors.Patients and Methods: A cross-sectional survey was conducted in Jiading District, Shanghai, targeting caregivers of children and adolescents attending elementary, middle, and high schools. Data on caregiver-reported ADHD, demographic characteristics, and related health conditions were collected. Descriptive statistics, bivariate and logistic regression analyses were employed to examine the prevalence and factors related to caregiver-reported ADHD.Results: Overall, 12.64% of caregivers reported that their child had ADHD. Factors associated with caregiver-reported ADHD included male gender, younger age (elementary school), and conditions such as tic disorders, short stature, and anorexia.Conclusion: The prevalence of caregiver-reported ADHD was found to be nearly twice the estimated national prevalence, potentially reflecting increased awareness and better screening in urban, highly developed areas like Shanghai. However, limitations related to caregiver-reported ADHD should be considered, as symptoms may be misinterpreted due to personal perceptions, cultural biases, and the broad diagnostic criteria of ADHD. Given the potential for over- or under-diagnosis in caregiver-reported ADHD, healthcare providers and educational systems should work to enhance awareness, implement systematic screenings, and provide targeted health education to caregivers and schools to ensure accurate diagnosis and timely intervention.Keywords: attention deficit hyperactivity disorder, ADHD, caregiver-reported, prevalence, associated factors, diagnosis, Shanghai